Pertimbangan Hakim Dalam Penjatuhan Putusan Terhadap Tindak Pidana Pencurian Oleh Anak Di Pengadilan Negeri Kelas I A Kupang - Devid M. Kalelena; Renny R Masu; Windasari Novelia Sudiarta (Law Faculty, Nusa Cendana University, 2026)
Juvenile theft represents a pressing issue within the criminal justice system, requiring a distinctive approach that balances legal accountability with the imperative of child protection and rehabilitation. This study aims to examine and analyze the legal considerations employed by judges in rendering verdicts against children who commit theft, with a specific focus on a case adjudicated by the Class IA District Court of Kupang. Utilizing a normative juridical method, the research applies statutory and case-based approaches. Data were collected through literature review and the analysis of court decisions. The findings reveal that judicial considerations extend beyond the formal legal requirements outlined in Article 362 of the Indonesian Criminal Code. Judges also evaluate non-juridical aspects such as the child’s family background, age, education level, remorse, and recommendations from the Correctional Center (Balai Pemasyarakatan). The verdicts rendered prioritize rehabilitative and developmental outcomes over punitive measures, reflecting a restorative justice model. This approach aligns with the best interest of the child principle, as mandated by Law No. 11 of 2012 on the Juvenile Criminal Justice System. The study underscores the importance of a child-centered legal response that not only addresses criminal accountability but also fosters reintegration and future development. It calls for consistent application of rehabilitative justice in juvenile cases to ensure both legal certainty and humane treatment of child offenders.